CALCULATION OF THE IRRADIATION DOSE FOR SOME COMPONENTS OF THE FOOD CHAIN OF THE FRESHWATER ECOSYSTEM OF THE YENISEI RIVER, DURING THE OPERATION OF THE NUCLEAR FUEL CYCLE ENTERPRISE – THE MINING AND CHEMICAL COMBINE, KRASNOYARSK - V. N. Rakitsky; L. G. Bondareva; N. E. Fedorova (Радиационная гигиена)
This study is focused on the evaluation of the levels of accumulation of the man-made radionuclides by several components of Yenisei River close to the water discharge spot of the Mining and chemical plant containing a significant amount of man-made radionuclides. The study was performed during the period of activity of the third nuclear reactor, belonging to this facility and included measuring the concentration of the gamma-emitting man-made and natural radionuclides. Gamma-spectrometry indicated significant amounts of man-made activation radionuclides (24Na – up to 1950 Bk/kg, 51Cr – up to 2860 Bk/kg) in biological objects. With some assumptions at the dose rate assessment, the highest does were estimated for the following organisms (mkGy/day): water plants – up to 39, fish – grayling 22,3 and pike 36,4. These values are significantly lower compared to the accepted dose from ionizing radiation for the water biota – 10 mkGy/day.